Acral Peeling Skin Syndrome Resembling Epidermolysis Bullosa Simplex in a 10-Month-Old Boy - S. Kavaklieva; I. Yordanova; L. Bruckner-Tuderman; C. Has (Karger Publishers, 2013)
The acral peeling skin syndrome (APSS) is a rare autosomal recessive disorder clinically characterized by asymptomatic desquamation of the skin limited to the hands and feet and histologically by cleavage at the stratum granulosum and stratum corneum level [Kiritsi et al.: J Invest Dermatol 2010;130:1741-1746]. We report on a 10-month-old boy with a history of skin peeling limited to the hands and feet since 2 months of age. Clinical examination revealed erythematous erosions with peripheral desquamation and flaccid blisters. DNA mutation analysis detected two heterozygous TGM5 mutations: c.2T>C, p.M1T in exon 1 and c.337G>T, p.G113C in exon 3 in keeping with the diagnosis of APSS. The clinical presentation of APSS alone might be confusing and strongly resemble epidermolysis bullosa simplex making the differential diagnosis difficult.